2009
DOI: 10.1089/met.2008.0025
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and β Cell Function As Prognostic Indicator in Multi-Organ Dysfunction Syndrome

Abstract: Insulin resistance (IR) is a major factor in the pathogenesis of sepsis. Critically ill patients with multi-organ dysfunction syndrome (MODS), diagnosed as per modified Acute Physiology and Chronic Health Evaluation II (modified APACHE II) score criteria and admitted to the medical ward in our hospital, were assessed for IR and beta cell function by using the homeostasis model assessment A (HOMA-A) and HOMA-B models, respectively. Of 80 consecutive patients, 60 were followed up to day 7; 16 patients died and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 23 publications
(25 reference statements)
2
18
0
1
Order By: Relevance
“…Ultimately, when the liver cannot maintain glucose production from fatty acids, blood triglyceride concentrations increase. Similarly, hypertriglyceridemia is the main feature of altered fat metabolism in critically ill humans 23 . In calves, glucose concentrations decrease and triglyceride concentrations increase in response to administration of endotoxin or TNF‐α 58 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, when the liver cannot maintain glucose production from fatty acids, blood triglyceride concentrations increase. Similarly, hypertriglyceridemia is the main feature of altered fat metabolism in critically ill humans 23 . In calves, glucose concentrations decrease and triglyceride concentrations increase in response to administration of endotoxin or TNF‐α 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Insulin also has anti‐inflammatory properties by decreasing inflammatory cytokines and enhancing anti‐inflammatory mediators, 18 which may confer some therapeutic benefit in patients in a proinflammatory state (eg, septicemia or endotoxemia). Insulin resistance is a common feature of sepsis and endotoxemia in humans 21,23 and also has been reported in horses 24,25 …”
mentioning
confidence: 91%
“…Insulin resistance and beta cell dysfunction has been associated with the development of MODS [79,80]. In Type 2 diabetes more than 150 genetic loci are associated with the development of diabetes and 50 candidate genes have shown to play a major part in the development of the disease [81].…”
Section: Scn Dysfunction In Diabetes With Relevance To Modsmentioning
confidence: 99%
“…Previous studies also showed the FBS, FIL and HOMA IR values were increased in cases with sepsis and MODS than in controls. 6,7 In our study it was observed that insulin resistance was significantly higher (64.5%) among non survivors than survivors (13.6 %) showing that patients with insulin resistance had increased risk of mortality. The values between the groups was statistically significant with chi-Square value 20.79 and p=0.000.…”
Section: Results and Observationsmentioning
confidence: 53%